2017
DOI: 10.1200/jco.2017.35.4_suppl.252
|View full text |Cite
|
Sign up to set email alerts
|

Resminostat and sorafenib combination therapy for advanced hepatocellular carcinoma in patients previously untreated with systemic chemotherapy.

Abstract: 252 Background: Resminostat is an oral hydroxamate-type inhibitor of class I, IIB, and IV histone deacetylases. A European Phase II study of second-line combination therapy with resminostat and sorafenib for hepatocellular carcinoma (HCC) in patients (pts) revealed a promising improvement in overall survival (OS). Here we report the findings on safety and efficacy of an Asian Phase I/II study on first-line combination therapy with sorafenib and resminostat in HCC pts. Methods: Pts with advanced or metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Another HDAC inhibitor, romidepsin [ 67 ] belonging to the family of depsipeptide natural products was approved for CTCL. Sipruchostatin, also belonging to the class of natural product depsipeptide is currently undergoing phase 1 clinical investigation for the treatment of solid tumors [ 198 , 199 ]. Belinostat (PXD-101) that bears a more rigid alkenyl hydroxamic acid is the third HDAC inhibitor to be approved by US FDA in 2014 [ 69 ] for the treatment of PTCL.…”
Section: Epigenetics Tools For Cancer Therapy In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Another HDAC inhibitor, romidepsin [ 67 ] belonging to the family of depsipeptide natural products was approved for CTCL. Sipruchostatin, also belonging to the class of natural product depsipeptide is currently undergoing phase 1 clinical investigation for the treatment of solid tumors [ 198 , 199 ]. Belinostat (PXD-101) that bears a more rigid alkenyl hydroxamic acid is the third HDAC inhibitor to be approved by US FDA in 2014 [ 69 ] for the treatment of PTCL.…”
Section: Epigenetics Tools For Cancer Therapy In Cancermentioning
confidence: 99%
“…In phase II study, 170 pts were enrolled and the results demonstrated a median time to progression of 2.8 months in the combination and control arm. Significant difference was not observed in the median OS (NCT02400788) [ 199 ] Resminostat was also tested in R/R HL in a phase 2 study and the results demonstrated clear OR in R/R HL patients. Moreover, the drug was found to be endowed with excellent safety profiles in heavily pre-treated patient population (NCT01037478) [ 200 ] In a phase I/II study conducted in japanese patients with stage IIIB/IV or recurrent NSCLC and prior platinum-based chemotherapy, no DLT was observed in phase I part and the recommended dose was determined to be 600 mg/day with 75 mg/m 2 of docetaxel.…”
Section: Epigenetics Tools For Cancer Therapy In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Current treatment regimens often are not effective because of the late stage of diagnosis and the inability to deliver the correct therapeutic dose to the liver [2]. Over the past few years, more effort has been concentrated in the development of multifunctional [3,4,5] or combination therapy [6,7,8] in order to improve existing anticancer treatments. This strategy has previously identified that combination therapy can result in synergy and overall can improve efficacy of therapies, as well as reduced drug resistance.…”
Section: Introductionmentioning
confidence: 99%